Stakeholders' Perceptions of Factors Influencing the Use of Take-Home-Naloxone - Taylor J. Holland; Jonathan Penm; Jacinta Johnson; Maria Sarantou; Betty B. Chaar (MDPI AG, 2020)
Background and Aims: Opioid associated death and overdose is a growing burden in societies all over the world. In recent years, legislative changes have increased access to naloxone in the take-home setting for use by patients with a substance use disorder and bystanders, to prevent opioid overdose deaths. However, few studies have explored the factors influencing the uptake by its multiple stakeholders. The aim of this scoping review was to explore the factors influencing the use of take-home naloxone from the perspectives of different stakeholders. Methods: A scoping review methodology was adopted with a systematic search of databases EMBASE, MEDLINE and PubMed. A variation of the search words "naloxone", "opioid" and "overdose" were used in each database. The articles were screened according to the predetermined inclusion/exclusion criteria and categorized based on their key perspective or target population. Results: The initial database search yielded a total of 1483 articles. After a series of screening processes, 51 articles were included for analysis. Two key stakeholder perspectives emerged: patients and bystanders (n = 36), and healthcare professionals (n = 15). Within the patient and bystander group, a strong consensus arose that there were positive outcomes from increased access to take-home naloxone and relevant training programs. Despite these positive outcomes, some healthcare professionals were concerned that take-home naloxone would encourage high-risk opioid use. Conclusion: Take-home naloxone is slowly being introduced into community practice, with a sense of enthusiasm from patients and bystanders. There are still a number of barriers that need to be addressed from healthcare professionals' perspective. Future research should be aimed at emergency care professionals outside of the US, who are most experienced with naloxone and its potential impact on the community.